Pattern of congenital anomalies among pediatric surgical patients in a tertiary care hospital in northern Tanzania - Faraja Mussa Magwesela; Happiness Rabiel; Catherine Mlelwa Mung'ong'o (BMJ Publishing Group, 2022)
Background Congenital anomalies are major causes of morbidity and mortality in children under 5 years of age and make a significant contribution to the surgical burden of diseases. Most anomalies have multifactorial causes and commonly affect the central nervous, cardiovascular, gastrointestinal and musculoskeletal systems. Countries with improved pediatric surgical care have shown dramatic reductions in morbidity and mortality rates. The aim of this study was to analyze the pattern of congenital anomalies presenting in our surgical departments in patients under 5 years of age.Methods A retrospective descriptive study was done. Data were obtained from clinical records of patients under 5 years of age, who underwent surgical correction of their congenital anomalies between 2017 and 2021. Analysis was done to identify the proportion of congenital anomalies managed in our setting.Results Congenital anomalies contributed 4.6% of overall surgical burden. Totally, 822 patients with congenital anomalies were included for analysis. The most commonly diagnosed congenital anomaly was inguinal hernia, followed by hydrocephalus, neural tube defects and cleft lips. The most commonly affected system was the central nervous system, anterior abdominal wall, orofacial and digestive system in decreasing order of frequency. Most of our patients presented outside the neonatal period (84.4%), and few (16.1%) had more than one system affected. Male children comprised 64%.Conclusions Delayed presentation of children with congenital anomalies is still a significant problem in our area. Prevention through nutritional supplementation and antenatal screening is crucial. The true epidemiology of congenital anomalies in northern Tanzania is still obscure.